1987
DOI: 10.1002/fam.810110102
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature on the gaseous products and toxicity generated from the pyrolysis and combustion of rigid polyurethane foams

Abstract: The literature on rigid polyurethane foam has been reviewed with an emphasis on the gaseous products generated under various thermal decomposition conditions and the toxicity of those products. This review is limited to publications in English through 1984. Carbon monoxide (CO) and hydrogen cyanide (HCN) were the predominant toxicants found among more than a hundred other gaseous products. The generation of CO and HCN was found to increase with increasing combustion temperatures. Many test methods were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…4 2,4-TDI (i) and 2,6-TDI (ii) secondary decomposition mechanism where isocyanates trapped in the condensed phase are converted irreversibly into their amine derivatives. A review by Paabo and Levin (1987) found that there is no difference in the decomposition products of rigid and flexible polyurethane foams at high temperatures regardless of their differing degradation mechanisms at lower temperatures. Both types of foam yielded very similar products at temperatures above 600°C.…”
Section: High Temperature Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 2,4-TDI (i) and 2,6-TDI (ii) secondary decomposition mechanism where isocyanates trapped in the condensed phase are converted irreversibly into their amine derivatives. A review by Paabo and Levin (1987) found that there is no difference in the decomposition products of rigid and flexible polyurethane foams at high temperatures regardless of their differing degradation mechanisms at lower temperatures. Both types of foam yielded very similar products at temperatures above 600°C.…”
Section: High Temperature Decompositionmentioning
confidence: 99%
“…Polyurethane foams based on polyether polyols will have a lower decomposition temperature in air than polyester polyol based foams. However, as noted by Paabo and Levin (1987), many studies into the decomposition of polyurethane foams do not differentiate between flaming and non-flaming decomposition, and focus on the temperature of decomposition rather than the presence of flames. Therefore, in certain conditions, polyurethanes foams can reach their auto-ignition temperature and ignite which will significantly alter the effect the decomposition mechanisms and resulting products.…”
Section: General Decomposition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The 276 production of both compounds increased with temperature as a consequence of the thermal 277 degradation of heavier compounds (Paabo and Levin, 1987).…”
mentioning
confidence: 99%
“…Initially many studies were qualitative and investigated which organic species could be expected in fire gases as most previous experience of the characterisation of combustion gases was from controlled combustion rather than fires, e.g. the groundbreaking work of Levin et al at NIST [5][6][7][8][9][10]. It was not until the 1990s that large volumes of quantitative data concerning fire gas characterisation were first published to a great degree, such as that produced by SP [11][12][13].…”
Section: Introductionmentioning
confidence: 99%